2017
DOI: 10.1007/s00134-017-4785-1
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent noninvasive ventilation after extubation in patients with chronic respiratory disorders: a multicenter randomized controlled trial (VHYPER)

Abstract: Early NIV performed following a sequential protocol for the first 48 h after extubation decreased the risk of respiratory failure in patients with chronic respiratory disorders. Reintubation and mortality did not differ between NIV and conventional oxygen therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 39 publications
1
44
0
3
Order By: Relevance
“…After excluding 334 duplicates and 3134 irrelevant citations, we reviewed the full text of the remaining 62 records. Finally, a total of 17 eligible RCTs [23,[26][27][28][37][38][39][40][41][42][43][44][45][46][47][48][49], representing 3341 patients, were included in this NMA. The PRISMA flowchart for study inclusion is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…After excluding 334 duplicates and 3134 irrelevant citations, we reviewed the full text of the remaining 62 records. Finally, a total of 17 eligible RCTs [23,[26][27][28][37][38][39][40][41][42][43][44][45][46][47][48][49], representing 3341 patients, were included in this NMA. The PRISMA flowchart for study inclusion is shown in Fig.…”
Section: Study Selectionmentioning
confidence: 99%
“…Of the 17 included RCTs [23,[26][27][28][37][38][39][40][41][42][43][44][45][46][47][48][49], 10 [23, 26-28, 38, 41, 43-46] were multicenter, and 7 [37,39,40,42,[47][48][49] were single-center. All included RCTs were published in the last 15 years, and the number of participants ranged from 38 to 614.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Studies showed that after a planned extubation, preventive use of NIV was associated with reduced risk of reintubation in patients with these risk factors. [18][19][20]31 In our study, we did not predefine how NIV should be used after extubation. The attending physicians were more likely to order the use of NIV in patients with risk factors.…”
Section: Discussionmentioning
confidence: 98%
“…Für einen generellen prophylaktischen Einsatz der NIV nach konventionellem Weaning gibt es keine positiven Daten betreffend die Endpunkte Mortalität oder Re-Intubation, jedoch Empfehlungen bei Hochrisikopatienten, zu denen COPD-Patienten gezählt werden. [26,27]. NIV bei neuerlichem respiratorischem Versagen nach Extubation (Postextubation Failure) zeigt keinen Vorteil [28,29].…”
Section: Weaning Bei Copdunclassified